Uterine Artery Doppler Velocimetry in the Prediction of Pre-Eclampsia - Akinboboye, Waleola H.; Benedict, Ekaidem; Ozori, Ebiogbo Stanley; Okpara, Abuchi L.; Alabintei, Ochuko M.; Ogidigba, Peter I. (British Journal of Healthcare and Medical Research, 2022)
A major goal towards improving antenatal management of pre-eclampsia is to develop accurate prediction model that identifies women at high risk of this disease for appropriate interventions. The objective of this study was to evaluate the usefulness of uterine artery Doppler screening at 18-20 weeks gestation in predicting the development of preeclampsia. This study involved 100 healthy pregnant women between the gestational ages of 18-20 weeks with singleton fetus recruited from the antenatal care clinic. All the women had uterine artery Doppler ultrasonography done. Abnormal results were defined as systolic/diastolic (S/D) ratio, resistivity index > 95th centile and the presence of a uterine artery diastolic notch. All participants were followed up till delivery and outcome measure (development of preeclampsia) was obtained from antenatal records. The statistical significance level was set at P < 0.05. There was significant association between an abnormal uterine artery S/D ratio (χ2 = 9.34, P = 0.02), uterine artery R.I (χ2 = 9.53, P = 0.02), uterine artery diastolic notch (χ2 = 13.46, P = 0.01), and the combined uterine artery indices (χ2 = 14.26, P = 0.001) with subsequent development of Preeclampsia. It was concluded that abnormal uterine artery Doppler indices were associated with development of Preeclampsia and may be considered as a tool to be used in screening for Preeclampsia.